I Templi Megalitici di Malta e Gozo - un’applicazione GIS per la documentazione - Baratin, Laura; Bertozzi, Sara; Moretti, Elvio (Archeomatica, 2017)
Many megalithic structures are to be found on the islands of Malta and Gozo, and they have been declared a world heritage by the UNESCO. They have undergone detailed archaeological investigation, begun in past centuries and still going on. This led the Maltese institutions to launch a campaign, in 2004, to document, safeguard and promote these important signs of a past civilization. The results of a vast operation involving surveying and data processing, followed by integration into the GIS system, are presented here. They start from historical and archaeological documentation, comprehension of the territorial context of the megalithic structures, topographic survey campaigns and laser scanning of 5 temples with all the delicate and complex post-processing operations, proceeding to data management with GIS systems. Archaeological studies often interface with various tools developed by new technologies, and it is therefore important to understand how they can interact among each other and what are the main issues which can arise in moving among systems in order to reply in the best way to the need to safeguard and promote this heritage.